STUDI KUANTITATIF : EFISIENSI KERJA DAN MANAJEMEN WAKTU DALAM MENINGKATKAN KINERJA PETUGAS 3R DI LINGKUNGAN KECAMATAN PENJARINGAN, JAKARTA UTARA - Novianti, Della Suci; Permatasari, Rita Intan; Veritia, Veritia (LPPM University 17 Agustus 1945 Samarinda, 2024)
Performance is a person's ability or the results achieved by a person in carrying out the tasks assigned to them, both in terms of quality and quantity, achieved in a given period of time in accordance with the responsibilities assigned to them. This study aims to determine and analyse the effect of work efficiency and time management on the performance of 3R (Reduce, Reuse, Recycle) officers in the office of the Environmental Implementation Unit of Penjaringan District. The research method uses a quantitative approach that is associative in nature with inferential (inductive) statistical analysis techniques. The research sample was 3R officers as many as 36 people with saturated sampling technique. The results of this study indicate that the Work Efficiency variable has a partial effect on performance of 0.308 and the Time Management variable has a partial effect on performance of 0.698. Work Efficiency and Time Management variables simultaneously affect performance by 66.5%.